Zjawisko mobbingu a budowanie zaufania w organizacji - Rybak, Mirosława (Annales. Etyka w Życiu Gospodarczym, 2008)
The purpose of this paper is to attract attention to the extent of mobbing, especially in the public sector and to its destructive character. Mobbing reduces the value of human capital because of incurred psychological and health losses. It influences innovation negatively and in consequence leads to lowering the effectiveness of an organization. Negative effects of mobbing may be also seen in the social and individual dimensions. According to Heinz Leymann, abandoning moral norms, wrongly comprehended tolerance are creating a climate for practising different forms of hidden violence and psychical terror. Psychological war of this kind in workplace involves the abuse of power and manipulation. Once it has appeared, it is – as put by M.F. Hirigoyen – like a machine, which set in motion, may smash everything on its way. This asymmetric and destructive interaction can only keep strengthening unless someone from the outside intervenes decisively. Yet, the introduction of the notion of mobbing to labour code does not provide sufficient protection from mobbing in workplace – regulations leave too wide, unfilled space which needs to be filled up with concrete solutions and measures. On one hand, action taken by an organization should have a formal, administrative and organizational character. On the other hand, it should take into account the ethical sphere of an organization’s functioning. It should put special emphasis on the maintenance and the development of integrity, one of the most important dimensions of the conception of trust.